Using critical race mixed methodology to explore the experiences of African Americans in education. Issue 4 (1st October 2020) - DeCuir-Gunby, Jessica T.
Abstract: The goal of this article is to explore the relationship between a researcher's inquiry worldview and methodological choices. In the analysis, I explicate my own racialized positionality and Critical Race Theory (CRT) inquiry worldview. Also, I explain my use of critical race mixed methodology (CRMM), the combining of CRT and mixed methods. In doing so, I give specific examples from my program of research. The discussion ends by my providing implications for conducting CRMM in educational psychology.